ANALISIS TEKSTUAL LIRIK LAGU “BERITA KEPADA KAWAN” - NFN Nursyamsi (Multilingual, 2014)
As the text, song is a sistem tanda which has been organized by the codes which has reflected the certain value, behaviour, and believed. As a discourse, song has a complete and sound concept. It as also complete message, cohesive in form and coherence in meaning. This paper is arranged to reveal the discourse of song lyrics “Berita kepada Kawan” by Ebiet G. Ade taken from textual, thatconsists of grammatical and lexical aspect. The method applied are library method, analyticdescriptive, and narative arrangement. The textual aspect analysis has result that gramatical aspect which is applied in the song lyric are reference (personal, demonstrative, and comparative reference), ellipsis, and conjunction. Lexical aspects are repetition (anaphore, epizeuksis), synonymy, collocation, antonymy, and hyponimy.